Cola Nitida (Kola-Nut) Enhances Gastric Ulceration and Secretion Via Ileum Motility Increase - EO, Jimmy; P.S, Inyang; IU, Umoh (Journal of Diseases, 2019)
Ileum motility, gastric ulceration and secretion were studied in thirty albino rats in the administration of the ethanolic extract of cola nut. The acute toxicity study in 27 mice showed the LD50 of 1118.03mg/kg established through 100% mortality in group with 5000mg/kg and 0% mortality with 1000mg/kg. Three orthodox drugs for ulcer treatment: cimetidine ranitidine and omeprazole were used in the study to compare motility, gastric ulceration and secretion with cola-nut. The motility of the ileum expressed as basal height of contraction was significantly higher (P <0.05) in groups administered with low, medium and high dosages of the extract compared with control groups using distilled water and atropine. However, there was a significant decrease ((P <0.05) in the ileum motility in the group administered with medium dose, extract of omeprazole than in cimetidine and ranitidine. Motility was significantly (P <0.05) higher in groups administrated with the extract plus ranitidine and cimetidine than groups administered with the medium extract dose and omeprazole. Gastric acid output was increased in the group administered with a high dose of the extract of cola nut and was significant (P <0.05) among the groups. Gastric ulceration was significantly higher (P <0.05) in the groups administered with the extract than in the omeprazole, cimetidine and ranitidine control groups. It is concluded that cola nut is very ulcerogenic i.e. it can lead to ulcer in its consumption and should be avoided particularly in gastric ulcer patients.